2003
DOI: 10.1007/s00775-002-0401-z
|View full text |Cite
|
Sign up to set email alerts
|

Backbone dynamics and hydrogen exchange of Pseudomonas aeruginosa ferricytochrome c 551

Abstract: A model-free analysis of Pseudomonas aeruginosa ferricytochrome c(551) dynamics based on (15)N R(1), (15)N R(2), and [(1)H]-(15)N heteronuclear nuclear Overhauser effect data is reported. The protein backbone is highly rigid (< S(2)>=0.924+/-0.005) and displays little variation in picosecond-nanosecond time scale dynamics over the structure. The loop structure containing the axial methionine ligand (loop 3) displays anomalous rigidity, which is attributed to its high proline content. Also reported are protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 42 publications
(75 reference statements)
7
73
0
Order By: Relevance
“…The yields we report for AzHm-14 are similar to those of several cyts c overexpressed in E. coli, with the latter having a range of 1-12 mg/L. [27][28][29] The extent of heme attachment to the CXXCH motif has been shown not to depend on the amount of apoprotein having a heme binding motif in the periplasm. 30 To explain this observation, it has been suggested that the availability of free heme transported to the periplasm by an unknown mechanism may determine the yield of protein modified with heme.…”
Section: Discussionsupporting
confidence: 64%
“…The yields we report for AzHm-14 are similar to those of several cyts c overexpressed in E. coli, with the latter having a range of 1-12 mg/L. [27][28][29] The extent of heme attachment to the CXXCH motif has been shown not to depend on the amount of apoprotein having a heme binding motif in the periplasm. 30 To explain this observation, it has been suggested that the availability of free heme transported to the periplasm by an unknown mechanism may determine the yield of protein modified with heme.…”
Section: Discussionsupporting
confidence: 64%
“…Pa cyt c 551 WT and F7A mutant was prepared as previously reported (33,52). The resonance Raman system (29) and the femtosecond VCS system used in this work have been described in detail elsewhere (26)(27)(28)(29).…”
Section: Methodsmentioning
confidence: 99%
“…Two-dimensional NMR studies have elucidated the structural and dynamical details of solvated proteins on time scales longer than tens of picoseconds. 13,[25][26][27][28][29][30][31][32][33] Multidimensional IR spectroscopy has improved upon the dynamic range of NMR techniques, revealing biochemical dynamics that occur on the picosecond to femtosecond time scales. [34][35][36][37][38][39][40][41] Vibrational echo spectroscopy is a multidimensional IR technique that is sensitive to the relationship between structure and dynamics in heme proteins.…”
Section: Introductionmentioning
confidence: 99%